Hyposensitisation with house dust mite vaccine in bronchial asthma. Issue 6035 (4th September 1976) - Gaddie, J; Skinner, C; Palmer, K N
Abstract : In a double-blind placebo-controlled trial of tyrosine-absorbed Dermatophagoides pteronyssinus vaccine no improvement was seen in 45 patients with asthma sensitive to house dust mite. In particular there was no significant improvement in symptom scores, spirometry, and skin and nasal challenge test results. Some patients in other studies have benefited from doses of vaccine much stronger than those now commercially available, but the incidence of side effects has also been high.